PHENOMENOLOGICAL WAVE MODEL OF THE SEISMIC PROCESS - Vikulin A.V. (My University, 1990)
The long-term seismic forecasts for the island arcs and continental margins of the Pacific Ocean have proved to be correct in a quite large (80 to 90) percentage of cases. This fact suggests that the statistical methods used to elucidate the cyclicity of the seismic process are adequate to this task. This paper presents a joint analysis of the lateral, temporal and energy distributions of earthquakes of magnitude M ≥ 7 that have occurred between 1904 and 1986. On the northwestern margin of the Pacific Ocean (the Japan, the Kurile-Kamchatka and the Aleutian Island arcs). The distributions themselves were derived by statistical analysis. Results, suggests that on the margin of the Pacific Ocean the seismic process is represented by countercurrent seismicity waves traveling along the rim with periods and wavelengths equal to the length of the seismic cycle and to the focal dimensions of the strongest earthquakes, respectively. In such a model, two seismogeodynamic parameters become physically important.